Impulsivity as a Risk Factor for Suicide in Bipolar Disorder - Zakowicz, Przemysław; Skibińska, Maria; Wasicka-Przewoźna, Karolina; Skulimowski, Bartosz; Waśniewski, Filip; Chorzepa, Aneta; Różański, Maciej; Twarowska-Hauser, Joanna; Pawlak, Joanna (Frontiers in Psychiatry, 2021)
The accurate assessment of suicide risk in psychiatric, especially affective disorder diagnosed patients, remains a crucial clinical need. In this study we applied Temperament and Character Inventory, Barratt Impulsivity Scale, PEBL Simple Reaction Time test, Continuous Performance Task and Iowa Gambling Task to seek for variables linked with attempted suicide in bipolar affective disorder group (n=60; 17 attempters). The main findings were: the correlations between self-report tools scores and objective parameters of R<0.56; in CPT the difference between attempters and non-attempters was found in the number of correctly responded trials; in IGT only one parameter differed between attempters and non-attempters in BPI diagnosis; no significant differences between suicide attempters and non-attempters in TCI, BIS-11, and SRT were found. These justify the conclusion that impulsivity itself is not a strong predictor, and used as a single variable might not be sufficient to indicate the high suicide risk group among bipolar patients.